Engineered Bovine Serum Albumin Nanoparticles Incorporated Alpha Amylase Preparation for the Improved Activity (Global Journal of Science Frontier Research, 2014)
In the present study, the improved enzyme activity of alpha amylase encapsulated with bovine serum albumin nanoparticle (BSA) was carried out. Initially. The method for preparation of BSA nanoparticles was optimized with various parameters such as pH, acetone to BSA ratio, cross linking time and concentration of BSA. The optimal pH was found to be 4.5, 10 mg/ml of BSA concentration, acetone to albumin ratio was to be 4.5, cross linking time of 3hrs which gives the higher yield of BSA nanoparticles. The Nano-enzyme conjugate was prepared using the optimized conditions. The encapsulation of α-Amylase Enzyme with BSA Nanoparticle was done based on hydrophobic ion pairing (HIP) complexation. And the Scanning electron micrographs of BSA nanoparticle encapsulated enzyme at the targeted size of 100nm. Distinct changes in the kinetic parameters of nano albumin encapsulated α-amylase was observed. Enzyme activity of nano encapsulated alpha amylase was found to be maximum at the pH of 8.0, temperature 80ºC and 4.5mg/ml of substrate concentration.
Keywords: nano albumin; amylase; nanosphere; enzyme activity